2016
DOI: 10.4103/2231-0762.195517
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of child formula dentifrices containing different calcium and phosphate compounds on artificial enamel caries

Abstract: Objectives:Fluoride toothpaste has been extensively used to prevent dental caries. However, the risk of fluorosis is concerning, especially in young children. Calcium phosphate has been an effective remineralizing agent and is present in commercial dental products, with no risk of fluorosis to users. This in vitro study aimed to compare the effects of different calcium phosphate compounds and fluoride-containing dentifrices on artificial caries in primary teeth.Materials and Methods:Fifty sound primary incisor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The role of SLS was also considered important for strong adherence to the enamel surface and for uptake of mineralizing ions to enamel surface. [ 41 ] The high remineralizing capacity of the BAG Novamin observed in the current study may be attributed to its high content of calcium and phosphate and at the micro level where BAG plug could be more compact and intimately attached to the enamel surface. SEM analysis done in one study showed that the deposits formed by BAG Novamin were larger, more angular as compared to other remineralizing agents which can be attributed to high microhardness.…”
Section: Discussionmentioning
confidence: 78%
“…The role of SLS was also considered important for strong adherence to the enamel surface and for uptake of mineralizing ions to enamel surface. [ 41 ] The high remineralizing capacity of the BAG Novamin observed in the current study may be attributed to its high content of calcium and phosphate and at the micro level where BAG plug could be more compact and intimately attached to the enamel surface. SEM analysis done in one study showed that the deposits formed by BAG Novamin were larger, more angular as compared to other remineralizing agents which can be attributed to high microhardness.…”
Section: Discussionmentioning
confidence: 78%
“…Demineralization occurs when the pH of the oral environment drops below 5.5, allowing calcium and phosphate ions to diffuse from the enamel surface (Shen et al, 2015;Abou Neel et al, 2016). The duration and frequency of acid challenge can affect the level of damage to the tooth structure, which can range from small white spots to cavitation (Rirattanapong et al, 2017). It should be emphasized that when the enamel surface remains partially intact, there is an opportunity to stop carious lesions by the joint action of saliva minerals and fluoride therapy (Vanichvatana & Auychai, 2013;Farooq & Bugshan, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Toothpaste with fluoride can be more effective for enhancing remineralization, if tricalcium phosphate is added to it. It has been established that this agent delays the interaction of calcium with ionic fluoride, which allows more fluoride and calcium ions to be delivered to the demineralized enamel (Vanicvatana & Auychai, 2013;Rirattanapong et al, 2017). It should be noted that although fluoride ions are adsorbed on the surface of enamel crystals, preventing dissolution and enhancing remineralization, demineralized surface lesions remineralize faster and more fully than subsurface lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, CPP-ACP has shown superior efficacy to fluoride in caries management (38,39). By contrast, in 2016 Rirattanapong et al (47) reported that 500 ppm F toothpaste had a superior remineralization efficiency than CPP-APP.…”
Section: Discussionmentioning
confidence: 99%